Pengaruh Model Pembelajaran Rangking One Chemistry Quiz terhadap Motivasi dan Hasil Belajar Kognitif Siswa - Suryani, Erma; Hadiyanto, Abdul; Rahmaniah, Sri Ita (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2022)
The success of a teacher in the learning process does not depend on mastery of the material, but the teacher must be able to master the model or learning method used in the delivery of the material being taught. One of the models in question is the One Chemistry Quiz Ranking Learning model. The purpose of this study was to determine the effect of the Rank One Chemistry Quiz learning model on motivation and cognitive learning outcomes of seventh grade students of SMP Arinda Palembang 2019/2020. This type of research is experimental research, the research sample consists of two classes. The data collection technique was purposive sampling, class VII A as the experimental class and class VII B as the control class. The average value of cognitive learning outcomes in the experimental class was 74.56 and the control class was 68.70. Analysis of students' cognitive learning outcomes showed that the value of tcount > ttable was 1.93>1.61 at a significant level of 5%. In the experimental class, on average, students got the minimum criteria for completeness, while in the control class some students got the minimum criteria for completeness. The average learning motivation in the experimental class is 86.8% in the highly motivated category, while in the control class it is 70.86% in the motivated category. Thus, the Rank One Chemistry Quiz learning model can increase motivation and affect cognitive learning outcomes for seventh grade students of SMP Arinda Palembang in the 2019/2020 school year.